Abiotic and spatiotemporal factors affect activity of European bat species and have implications for detectability for acoustic surveys. Issue 2 (10th April 2020) - Perks, Samantha J.; Goodenough, Anne E.
Abstract : Bat activity surveys are essential in the contexts of scientific research, conservation, assessment of ecosystem health, monitoring progress towards sustainable development goals, and legislative compliance in development and infrastructure construction. However, environmental conditions have the potential to influence bat activity and, in turn, their detectability in acoustic surveys. Here we use 3242 hours of acoustic survey data from 323 nights of bat monitoring at 14 sites over a 4‐year period to explore the influence of spatiotemporal factors, lunar phase and weather conditions on bat activity. All spatiotemporal and abiotic factors analysed (site, hour post sunset, length of night, duration of moonlight, temperature, rain, wind and cloud cover) contributed to the optimal multivariate model for at least one bat species/genus; all factors except cloud cover and temperature were significant in the optimal model for total bat activity. However, there were notable species‐specific differences. Among the key findings were differences between Pipistrellus species, with periods of rainfall being negatively related to soprano pipistrelle Pipistrellus pygmaeus registrations but not those of common pipistrelle Pipistrellus pipistrellus . In addition, overcast conditions showed a strong positive relationship with the number of Myotis registrations while duration of moonlight was positively correlated with common pipistrelle. Temperature was only important for Nyctalus species. These findings demonstrate that understanding the effect multifaceted and interlinked environmental factors on the activity of different bat species is a vital step in developing maximally effective survey protocols, which, in turn, will improve the reliability of conservation and planning decisions underpinned by survey data.